Fundus autofluorescence imaging patterns in central serous chorioretinopathy according to chronicity - Lee, W J (Eye (Lond), 2016)
PURPOSE: To investigate the time-period characteristics associated with morphologic changes in central serous chorioretinopathy (CSC) using fundus autofluorescence (FAF). PATIENTS AND METHODS: Retrospective, cross-sectional observational case series. Patients were classified into three groups: acute and chronic according to the onset of subjective symptoms of 6 weeks and sequelae patients who have history and symptoms but no serous retinal detachment (SRD). We compared FAF images to obtain characteristic findings according to the chronicity. RESULTS: A total of 52 eyes were included in this study. Acute CSC eyes were characterized by decreased FAF intensity at the leakage point in 13/22 eyes (56.5%) and staining patterns with various levels of fluorescence signal (hyperautofluorescent (10 eyes, 43.5%), hypoautofluorescent (1 eye, 4.3%), and minimal changes (12 eyes, 52.2%)) in the area of SRD. In chronic CSC eyes, hyperautofluorescent (14 eyes, 63.6%) or minimal changes (8 eyes, 36.4%) were observed in the area of SRD. Discrete dots with increased FAF intensity were observed in chronic CSC eyes (P<0.001). Eyes with sequelae of CSC had mixed FAF patterns over areas of retinal pigment epithelium (RPE) atrophy in seven eyes (100%, P<0.001)) and descending tracts which showed various FAF intensities according to the RPE and photoreceptor status (P<0.001). CONCLUSION: FAF imaging patterns in CSC eyes differ according to the course of the disease, reflecting RPE and outer retinal changes. Detailed investigation using FAF could help to estimate the duration of CSC and determine the proper treatment modality.